Simulation of image fusion of dual modality (electrical capacitance and optical tomography) in solid/gas flow - Mohd Hafiz, Fazalul Rahiman; Rasif, Rasif; Ruzairi, Abd Rahim; Jaafar, Abdullah (Springer Verlag, 2010)
Link to publisher's homepage at http://www.springerlink.com/